Distant Reading Through Ontologies: The Case Study of Catania’s Benedictines Monastery - Claudia Cantale; Domenico Cantone; Marianna Nicolosi-Asmundo; Daniele Santamaria (JLIS.it, 2017)
In this contribution, we developed a Linked Open Dataset, more specifically an OWL ontology, about the history of the renovation of the Catania’s Benedictines Monastery by the architect Giancarlo De Carlo. We considered a wide subset of public and private documents collected from 1977 to 2006 during the process of restoration and adaptation of the monastery to a campus for the University of Catania.